Removal of persistent organic pollutants from water using a newly developed atmospheric plasma reactor. Issue 6 (18th January 2018) - Tampieri, Francesco; Giardina, Agata; Bosi, Franco J.; Pavanello, Alice; Marotta, Ester; Zaniol, Barbara; Neretti, Gabriele; Paradisi, Cristina
Abstract : A new bench‐top reactor employing a streamer discharge in air was developed and tested for potential use in an advanced oxidation stage in water treatment processes. The complex heterogeneous system and the ensuing chemical processes were characterized using an integrated approach to map the morphology of the plasma/gas/liquid interface, identify the plasma short‐lived excited species, determine the oxidants in solution and monitor the organic pollutants degradation. Three model pollutants were used in these experiments, rhodamine B, phenol and metolachlor. The first two are common standards used to evaluate the performance of advanced oxidation processes. Metolachlor is a widely used herbicide listed among the most important recalcitrant emerging organic pollutants. Energy efficiency, kinetics and products of our tests show a good performance of the reactor. Specifically, mineralization appears feasible also in the case of metolachlor. Abstract : A new reactor employing a streamer discharge in air is developed and tested for potential use in water treatment processes. The system was characterized using an integrated approach to map the morphology of the plasma/gas/liquid interface, identify the short‐lived excited species, determine the oxidants in solution, and monitor the organic pollutants degradation. Three model pollutants were used in these experiments: rhodamine B, phenol, and metolachlor.